Prevalence and Determinants of Antibiotic Dispensing Practices without Prescription in Community Pharmacies of Gadag City, India - Mushtaq, Junaid; Javeed, Bilkees (Indian Journal of Pharmacy Practice)
Background: Pharmacists play a crucial role in healthcare, ensuring the safe and effective distribution of medicines. However, the practice of dispensing antibiotics without prescriptions, particularly in India, raises significant concerns. This study aims to determine the extent of antibiotic dispensing practices without prescriptions across all drug outlets in Gadag City. Materials and Methods: A cross-sectional study was conducted in Gadag City, India, using semi-structured questionnaires. Universal sampling was employed, covering all 91 pharmacies, of which 83 participated. Data was analyzed using Excel and SPSS. Results: The study revealed that 92.7% of pharmacists dispense antibiotics without prescription. Patient demand for brand-specific antibiotics was high, with 79.5% of pharmacists noting patient insistence on particular brands, and the condition for which the antibiotics are most frequently dispensed is common cold and flu (92.8%). Conclusion: The findings reveal a significant disconnect between pharmacists’ knowledge of legal restrictions on dispensing antibiotics and their actual practices, with a large proportion still providing antibiotics without prescriptions. Pharmacists concern over losing business and patients’ financial constraints are key motivators for this practice. These findings underscore the urgent need for national-level policy enforcement and targeted educational programs to mitigate the risks of antimicrobial resistance.
Keywords: Antibiotic Prescription; Antimicrobial Resistance; Community Pharmacy; Non-Drug Prescriptions